PERENCANAAN KURIKULUM SDIT AL-YASMIN 2 KOTA BOGOR PASCA PANDEMI COVID-19 - Alifia Taufika Rahmah; Zahruddin Zahruddin; Maftuhah Maftuhah (Universitas Islam Negeri Sumatera Utara Medan, 2023)
As the times progress, it is also necessary to improve the quality of education in Indonesia, especially at the basic education level which is the first foundation for children in formal education. The Integrated Islamic School is a model educational institution that seeks to combine general knowledge and religious knowledge in one curriculum package. Thus, it is necessary to have a good understanding of curriculum management, especially in planning so that the goals of SDIT Al-Yasmin 2 Bogor City can be achieved. The method used in this study uses a qualitative descriptive approach. The results of the study show that in planning this curriculum, the institution involves the school principal, teachers, three deputy principals, school staff and school committees/guardians of students. In addition, there are school supervisors from the education office and heads of foundations as resource persons. This is done to meet all the needs of the community, especially those involved in the institution. The curriculum planning is carried out to determine graduation standards, the material studied and ways to develop students so that they are able to adapt to the changing times that are getting faster.Keywords: Planning, Curriculum, Integrated Islamic Elementary School